Intellectual capital: the dynamics of potential for organizational renewal - Martins, Ana (2014)
In the current knowledge economy, organisational assets have acquired intangible characteristics harnessing organisational sustainability. This study demonstrates the association between tangible and intangible assets to achieve an organisation’s full potential. The emerging claimed paradigm shift is externalised through human potential. An alternative viewpoint is proposed - how intellectual capital could be considered and measured. The umbrella term of human potential entails concepts of emotional, social and knowledge potentials. The model attempts to respond to the demands and challenges of the knowledge society on intellectual capital. Primary data obtained from a sample of postgraduate students based at University in the north of Portugal, shows questionnaire responses reveal an awareness of emotional and social capitals despite it loosing importance for those individuals who are gainfully employed. From this analysis, it can be inferred that human potential is a necessary condition albeit not in isolation.